THE INFLUENCE OF DIGITAL LITERACY AND DIFFUSION OF INNOVATION ON THE ADOPTION OF DIGITAL SERVICES AT THE REMBANG REGENCY PUBLIC SERVICE MALL - Ayu Hartiyanti, Zeldha Fitri; Kartika, Ray Septianis (Jurnal Administrasi Negara, 2025)
Public services in Indonesia still face challenges, including lengthy, complex, and inefficient bureaucracy. To address this, the government initiated the Public Service Mall (Mall Pelayanan Publik/MPP) as an integrated solution to improve efficiency and ease of access to services for the public. However, the implementation of MPPs in various regions, including Rembang Regency, still faces obstacles, especially in optimizing digital services. Examples include the absence of an online queuing system, incorrect operating hours on social media platforms, and a lack of website maintenance, all of which should be making services easier. This study aims to analyze the level of public adoption of digital public services at the Rembang Regency MPP. This research uses quantitative approach with the Unified Theory of Acceptance and Use of Technology (UTAUT), adding the variables of digital literacy and diffusion of innovation, which can predict the intention and use of information systems and help understand the factors that influence technology adoption. The results of this study show that digital literacy and diffusion of innovation together have a positive and significant effect on the public's acceptance of digitalization. These findings indicate that increasing digital literacy and accelerating the adoption of innovation are strategic factors in strengthening the success of digital public services. Therefore, the local government needs to strengthen the digital ecosystem, provide technical training, and promote innovation to continuously improve the effectiveness of the MPP.